Effects of wet corn gluten feed and intake level on diet digestibility and rumen passage rate in steers - Montgomery, Sean P.; Sindt, J.J.; Farran, T.B.; Pike, N.J.; Coetzer, C.M.; Trater, A.M.; Higgins, James J.; Drouillard, James S.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Including 40% wet corn gluten feed (WCGF) in the diet increased total tract digestion of organic matter and neutral detergent fiber (P<0.01), reduced total volatile fatty acid concentration (P<0.01), increased rumen NH3 concentration (P<0.01), increased rumen pH, and tended (P<0.06) to increase total tract digestion of starch. Furthermore, WCGF increased rumen passage rate of solid digesta (P<0.01) compared to diets containing no WCGF. Limit feeding reduced total tract digestion of organic matter and neutral detergent fiber (P<0.01), decreased total volatile fatty acid concentration (P<0.01), increased rumen NH3 concentration (P<.01), increased rumen pH at 0 and 12 hours after feeding, reduced rumen pH at 4 hours after feeding, and increased rumen liquid passage rate (P<0.02).
Keywords: Beef; Wet corn gluten feed; Limit feeding; Digestibility; Passage rate